Staring into a crystal ball: understanding evolution and development of in vivo aquatic organismal transparency - Hotta, Kohji; Miyasaka, Shunsuke O.; Oka, Kotaro; Shito, Takumi T. (Frontiers in Ecology and Evolution, 2024)
Organismal transparency is an ecologically important trait that can provide camouflage advantages to diverse organisms. Transparent organisms are quite common—especially in oceans. Organismal transparency requires low absorption and scattering of light in the body across multi-scale levels. However, it is still not fully understood how such organisms achieve these requirements. Understanding this process requires multiple approaches from various fields and methods. Here, we offer recent insights on this topic from the viewpoints of evolution, developmental biology, and evaluation methodologies of organismal transparency. We also propose “organismal transparency biology” as a new interdisciplinary field of study. Furthermore, we suggest that tunicates are an ideal model animal for studying in vivo organismal transparency.